Practical aspects modeling of air conveying modes for small–piece food products - Kryvoplias-Volodina, Liudmyla; Gavva, Oleksandr M.; Yakymchuk, Nikolai; Derenivska, Anastasiia; Hnativ, Taras; Valiulin, Hennadii (My University, 2020)
A mathematical and physical model of the critical pneumatic conveying modes has been developed to ensure the calculation and construction of pneumatic product pipelines of continuous operation. The model takes into consideration the technological conditions of gas suspension movement; the laws of movement of individual fine particles, accounting for their impact interaction and decompression, as well as the actual boundary conditions for a food product movement. The parameters of the zone of dynamic destruction of the layer of a small-piece food product by impact airwave were experimentally studied; the results of the calculation have been compared with the experimental data. The process of managing critical pneumatic conveying modes has been theoretically described, based on the proportional elements and feedback (a current loop of 4‒20 mA); the process of destruction of the cluster of products by airwave and controlled decompression has been studied. The process of pneumatic conveying of a small-piece product at the experimental bench system has been examined. As well as the process of moving the material in the product pipeline, which is controlled by compressed air pulses, to maintain the modes of operation. The following has been established: pressure losses caused by the movement of clean air; additional pressure losses resulting from the movement of the material; the loss of pressure required for transporting in a suspended state on a vertical stretch. A model has been developed to calculate the coordinates of a product particle when it collides with the inner surface of the product pipeline, as well as a change in its kinematic characteristics. The developed model makes it possible to determine the rational modes of pneumatic conveying and possible energy costs in the processing of various small-piece materials. The rational pneumatic conveying regimes have been determined, as well as possible energy costs in the processing of small-piece materials. As the time of supplying compressed air in the product pipeline increases, the number of product particles reaches a maximum in the range of 0.1...0.2 s. The compressed air flow rate, depending on the value of inlet mainline pressure P (0.1…0.3 MPa), is 80…160 (Nl/min). A general approach to the modeling of pneumatic conveying systems has been proposed
Keywords: pneumatic conveying; small-piece; excess pressure; feedback; gas suspension; пневмотранспортування; дрібно–штучні; надлишковий тиск; воротній зв’язок; газова суспензія; кафедра мехатроніки та пакувальної техніки